North Carolina [Un]incorporated: Place, Race, and Local Environmental Inequity. (July 2021) - Purifoy, Danielle M.
Research linking municipal underbounding to racialized environmental inequality suggests that understanding the built environmental outcomes of municipal annexation or incorporation may add an important dimension to scholarship on environmental justice and critical race theory. This article explores whether white, black, and Latinx populations are likely to receive the same built environmental benefits from municipal incorporation. I study the distribution and proximity of built amenities and disamenities across white, black, and Latinx populations in incorporated municipalities and unincorporated communities in North Carolina—a state with ongoing controversies about who benefits from municipal jurisdiction. To the extent that municipalities are associated with built environmental amenities, I find that block groups with high white populations are the primary beneficiaries. By contrast, environmental disamenities are distributed disproportionately in communities with higher black and Latinx populations regardless of municipal incorporation. These findings suggest that histories of racialized municipal exclusion are an additional layer of already overdetermined environmental racism, such that municipal inclusion—primarily through annexation of excluded black and Latinx populations—may do little to alter the existing inequities.